2022
DOI: 10.3389/fsufs.2022.1080481
|View full text |Cite
|
Sign up to set email alerts
|

Piper caninum extract and Brevibacillus agri mixture suppresses rice leaf spot pathogen; Nigrospora oryzae and improves the production of red rice (Oryza sativa L)

Abstract: Under the guise of enhancing productivity, using pesticides and artificial fertilizers in agriculture affects both the environment and living things. High chemical residues in food and the environment disrupt the health of consumers. One of the solutions that can bring about a reduction in the use of pesticides and chemicals is switching to organic fertilizers. The application of biopesticides originating from biological sources such as plant extracts and the use of microbes is gaining global acceptance. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…As previously reported, the ethanol extract and its acetonitrile fraction showed an IC 50 of 788 and 462 µg/mL on F. equiseti FCHE isolated from habanero pepper [ 29 ] (Cruz-Cerino et al, 2020). Other studies have previously reported the antifungal effect of Piper caninum leaf extract at 3% on Nigrospora orizae and Curvularia verriculosa pathogens on Oryza sativa [ 60 , 61 ]. The essential oils from P. neesianum leaves were identified as bicyclogermacrene, germacrene D, and β-caryopyllene (7.5%) and were major compounds among the 19 detected with gas chromatography coupled to mass spectrometry analysis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, the ethanol extract and its acetonitrile fraction showed an IC 50 of 788 and 462 µg/mL on F. equiseti FCHE isolated from habanero pepper [ 29 ] (Cruz-Cerino et al, 2020). Other studies have previously reported the antifungal effect of Piper caninum leaf extract at 3% on Nigrospora orizae and Curvularia verriculosa pathogens on Oryza sativa [ 60 , 61 ]. The essential oils from P. neesianum leaves were identified as bicyclogermacrene, germacrene D, and β-caryopyllene (7.5%) and were major compounds among the 19 detected with gas chromatography coupled to mass spectrometry analysis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%